2010
DOI: 10.1152/jn.00566.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ryanodine-Receptor-Dependent Ca2+-Activated K+ Currents and Hyperpolarizations in Rat Medial Preoptic Neurons

Abstract: The aim of the present study was to clarify the identity of slow spontaneous currents, the underlying mechanism and possible role for impulse generation in neurons of the rat medial preoptic nucleus (MPN). Acutely dissociated neurons were studied with the perforated patch-clamp technique. Spontaneous outward currents, at a frequency of approximately 0.5 Hz and with a decay time constant of approximately 200 ms, were frequently detected in neurons when voltage-clamped between approximately -70 and -30 mV. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…Our previous studies demonstrated that a majority of PHN neurons fire spontaneously, whereas some PHN neurons exhibit SMOCs (Saito & Yanagawa, ; Zhang et al ., ); these outward currents display slower kinetics compared with the postsynaptic currents and are induced by Ca 2+ ‐activated K + channels, which are activated by Ca 2+ ‐induced Ca 2+ release from the endoplasmic reticulum via ryanodine receptors (Arima et al ., ; Cui et al ., ; Klement et al ., ; Saito & Yanagawa, ). In the present study, most D+ neurons (67/70) exhibited spontaneous firing (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous studies demonstrated that a majority of PHN neurons fire spontaneously, whereas some PHN neurons exhibit SMOCs (Saito & Yanagawa, ; Zhang et al ., ); these outward currents display slower kinetics compared with the postsynaptic currents and are induced by Ca 2+ ‐activated K + channels, which are activated by Ca 2+ ‐induced Ca 2+ release from the endoplasmic reticulum via ryanodine receptors (Arima et al ., ; Cui et al ., ; Klement et al ., ; Saito & Yanagawa, ). In the present study, most D+ neurons (67/70) exhibited spontaneous firing (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Neurotransmitter receptors that also elevate cytoplasmic Ca 2+ levels, either by Ca 2+ influx through the receptor as in the case of NMDA receptors (Oliver et al, 2000;Faber et al, 2005;Ngo-Anh et al, 2005), or by triggering release of Ca 2+ from intracellular stores (Power and Sah, 2008;Klement et al, 2010), can also produce neuronal hyperpolarization by activating K Ca 2 channels. The trafficking of K Ca 2.2 channel subunits into and out of the spines on the dendrites of hippocampal neurons determines the onset and amplitude of longterm potentiation, a prolonged increase in excitatory synaptic transmission that follows repetitive synaptic stimulation of hippocampal pyramidal cells (Lin et al, 2008;Allen et al, 2011).…”
Section: The K Ca 2 Family-small Conductance Channels Regulated mentioning
confidence: 99%
“…These currents result from the activation of BK channels and lead to muscle relaxation. In a few neurons, similar currents called spontaneous miniature outward currents (SMOCs) have been detected that activate either SK channels (in rat medial preoptic neurons 129 ) or BK channels (in parasympathetic cardiac neurons 130 ). These studies did not determine in which part of the neuron the currents were activated nor did they suggest a clear consequence of their generation.…”
Section: Localized Events In Dendrites In Intact Preparationsmentioning
confidence: 99%